Fluorescent vapochromism in synthetic polymers. Issue 6 (5th April 2016) - Minei, Pierpaolo; Pucci, Andrea
Abstract : Nowadays, fluorescent vapochromic polymers are finding a permanent place in sophisticated measuring devices such as sensors thanks to their sensitivity, reversibility and rapid response Abstract : The detection of volatile organic compounds (VOCs) by means polymeric materials through fluorescence variations has attracted considerable interest over the past 10 years. The detection of VOCs is of great concern because of their undesirable impact on both the environment and human health. Moreover, the sensing of vapours of organic compounds such as explosives is one pressing issue in anti‐terrorism and homeland security. In this mini‐review, the current state of knowledge concerning the preparation of fluorescent polymers with vapochromic features is summarized. Two types of procedures are illustrated and thoroughly discussed along with their respective structure–property relationships: the first resides on the covalent insertion of chromophoric units into the macromolecule backbone or side chains; the second involves the physical dispersion of the fluorophore in a preformed polymer matrix. Herein we review the simplicity of the preparative routes available, and their influence over the properties of the resulting fluorophore–polymer systems, by focusing on the most illustrative examples described in the literature. Finally, conclusive remarks and future perspectives are presented and discussed. © 2016 Society of Chemical Industry